Exploring the Effects of Individual Formative Feedback on the Writing of Descriptive Texts among PINJ Level 2 Students (2024)
ABSTRACT: This action research study aimed to explore the effects of formative feedback on the writing of descriptive texts in a 2nd level course of Programa de Inglés para Niños y Jóvenes students. Under little exposure to writing development activities and lacking feedback in the few ones, this study proposed a series of writing activities supported on individual formative feedback, with a specific focus on five students of variable needs and writing abilities. This study followed a qualitative research framework with instruments such as teacher journals, recordings, and students’ artifacts to collect data. This study combined an action research design with a Descriptive Case Study method. Data collected stemmed from one pre-test, one post-test, teacher journals, audiorecordings of feedback, and students’ written artifacts. Findings show positive effects of formative feedback on students’ writings. Students used FF to validate and confirm both content and language knowledge, before and while writing. FF led students to apply instant corrections from word and sentence levels toward text level. Eventually, FF fostered mistake realization among learners, thus growing their writing confidence, achieving desired writing accuracy, or exploring meaning-making. Indeed, FF gave students the opportunity to ponder their knowledge, lead their own process, recognize their abilities, and tackle their own weaknesses. It also gave them the possibility of confronting needs and using learnings in upcoming writing activities.